Comparative Transcriptomic Analysis Reveals the Negative Response Mechanism of Peanut Root Morphology and Nitrate Assimilation to Nitrogen Deficiency - Lijie Li; Xiangguo Cheng; Xiangjun Kong; Peipei Jia; Xiaohui Wang; Lei Zhang; Xiaotian Zhang; Yi Zhang; Zhiyong Zhang; Baohong Zhang (Plants, 2023)
Root architecture plays a fundamental role in crop yield, which is sensitive to nitrogen fertilizer. Although it is well studied that nitrogen fertilizer significantly promotes peanut (Arachis hypogaea L.) growth and yield, less information was available on how its root development responds to nitrogen deficiency. In this study, the growth and development of roots were inhibited, as indicated by the significantly decreased root dry weight and length and the lateral root number, especially under 10 days of nitrogen deficiency treatment. The activities and the expression of the genes related to nitrogen assimilation enzymes including nitrate reductase, glutamine synthetase, glutamate dehydrogenase, and glutamine oxoglutarate aminotransferase and the genes encoding the nitrate transporters were significantly decreased under 10 days of nitrogen deficiency treatment, which may lead to a decrease in nitrate content, as indicated by the significantly decreased nitrogen balance index. Transcriptome sequencing revealed a total of 293 (119 up- and 174 downregulated) and 2271 (1165 up- and 1106 downregulated) differentially expressed genes (DEGs) identified after five and ten days of nitrogen deficiency treatments, respectively. Bioinformatic analysis showed that these DEGs were mainly involved in nitrate transportation and assimilation, phytohormone signal transduction, and the lignin biosynthesis pathway. Furthermore, a putative schematic diagram of nitrogen deficiency inhibiting root growth was established, which gives us a better understanding of nitrogen metabolism in peanut roots and a theoretical basis for improving nitrogen use efficiency.